2023
DOI: 10.1021/acscatal.3c02029
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CO2 Co-Feeding on the Stabilization of Atomically Dispersed Iron Species over MgAl2O4 During Ethane Dehydrogenation Reactions

Abstract: Ethane dehydrogenation provides an opportunity for the effective utilization of shale gas and production of ethene. Up to now, it is still a great challenge to acquire a stable ethane dehydrogenation catalyst operated under high temperature and reductive atmospheres. In this study, we prepared an Fe-based catalyst supported on MgAl 2 O 4 with atomically dispersed iron species even after 6 reaction−regeneration cycles. Sheet-like morphology and spinel structure of MgAl 2 O 4 is beneficial for the high dispersio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 62 publications
1
13
0
Order By: Relevance
“…The coke species could hardly be removed, which resulted in the passivation of those Co 0 species. According to our previous work, the generated coke species cannot be removed by CO 2 treatment under reaction conditions, hence, the dry-reforming active sites cannot be regenerated and the dehydrogenation reaction dominated when the feeding CO 2 /C 2 H 6 ratio was recovered to 4.0. Another experiment using a feeding CO 2 /C 2 H 6 ratio of 1.0 at the initial stage was performed and the catalytic performance is shown in Figure b.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The coke species could hardly be removed, which resulted in the passivation of those Co 0 species. According to our previous work, the generated coke species cannot be removed by CO 2 treatment under reaction conditions, hence, the dry-reforming active sites cannot be regenerated and the dehydrogenation reaction dominated when the feeding CO 2 /C 2 H 6 ratio was recovered to 4.0. Another experiment using a feeding CO 2 /C 2 H 6 ratio of 1.0 at the initial stage was performed and the catalytic performance is shown in Figure b.…”
Section: Resultsmentioning
confidence: 99%
“…11,14,16,23,33 Our previous studies found that co-feeding CO 2 can stabilize isolated Fe 3+ species over MgAl 2 O 4 and suppress the overreduction of FeO x over zeolite during alkane dehydrogenation reactions, leading to more stable catalytic performance compared with direct dehydrogenation reactions. 34,35 Xie et al indicated the dominative effect of CO 2 to prevent the reduction of active species (like Cr 3+ to Cr 2+ ) rather than eliminate coke deposition. 36 Liu et al discovered introducing CO 2 can suppress the formation of unfavorable Ga δ+ -H x species that resulted into a much stable propane dehydrogenation reaction.…”
Section: Introductionmentioning
confidence: 99%
“…For another irreducible type of catalysts (such as Ga- and In-based oxides), there may exist two tandem steps, direct dehydrogenation and RWGS, during the reaction . The introduction of CO 2 in dehydrogenation systems could promote reactions by consumption of H 2 along with an improvement of stability through removing coke via the Boudouard reaction and keeping metal in optimal oxidation states. , …”
Section: Progress On Spinel Catalysts For Thermal-driven C1 Conversionmentioning
confidence: 99%
“…The rational design of bifunctional catalysts is crucial to their catalytic performance in a targeted reaction. With dual metal and support active sites, it is usually possible to achieve synergistic catalysis by adjusting the metal, the support, and the interaction between the metal and the support. In the application of Pt/ZSM-5 in the alkylation of benzene with ethane, much work has been done in optimizing the morphology and acid property of the zeolite support. However, in-depth research on metal active sites is still insufficient.…”
Section: Introductionmentioning
confidence: 99%